Capital account liberalization and management - José Antonio Ocampo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
This paper reviews the history and controversies associated with capital account management. It first looks at the transition from the acceptance at the Bretton Woods conference of capital account regulations as a normal policy instrument to the liberalization of the capital account, first in developed countries and later in developing countries. This is followed by an analysis of the risks of capital account liberalization, particularly for emerging and developing countries, and the role and experience of capital account regulations as a complementary instrument of counter-cyclical macroeconomic policy, and as a financial stability tool - as part of the family of 'macroprudential regulations'.
Keywords: F02; F33; F36; 330; capital account regulations; capital account management; capital account liberalization